2009
DOI: 10.1524/zkri.2009.1175
|View full text |Cite
|
Sign up to set email alerts
|

X-ray crystal structure of synthetic REEAl2.07(B4O10)O0.60 (REE = (La, Ce); Ce; Nd) dimetaborates

Abstract: Aluminium dimetaborates / Rare earth elements (REE) / Peprossiite-(Ce) / Single crystal structure analysis / X-ray diffraction Abstract. NonstoichiometricREEAl 2.07 (B 4 O 10 )O 0.60 (REE ¼ (La, Ce); Ce; Nd) dimetaborates have been crystallized and analyzed by means of single crystal X-ray diffraction. The compounds resulted to be isostructural within hexagonal space group P62m (n. 189), with the following unit cell parameters: (6) A; c ¼ 9.3170(10) A and V ¼ 170.44(4) A 3 (Ce); a ¼ 4.5830(7) A, c ¼ 9.2810(14)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Then Capitelli, F. reported a detailed crystal chemical study of this compound by means of single crystal X-ray diffractometry and revised its formula to be LaAl 2.07 (B 4 O 10 )O 0.60 with cell parameters a = 4.61700(10) Å, c = 9.3640(3) Å and V = 172.86 Å 3 . 12 We believe that LaAl 1. Differential scanning calorimetric (DSC) measurements were carried out with crystal powders.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Then Capitelli, F. reported a detailed crystal chemical study of this compound by means of single crystal X-ray diffractometry and revised its formula to be LaAl 2.07 (B 4 O 10 )O 0.60 with cell parameters a = 4.61700(10) Å, c = 9.3640(3) Å and V = 172.86 Å 3 . 12 We believe that LaAl 1. Differential scanning calorimetric (DSC) measurements were carried out with crystal powders.…”
mentioning
confidence: 94%
“…S1 According to our knowledge, there are two flux systems that can grow LaAl 2.07 (B 4 O 10 )O 0.60 crystals, the K 2 Mo 3 O 10 flux system and the PbF 2 -PbO flux system. 12,13 Nevertheless, our earlier study of YAB revealed that the incorporation of Mo or Pb ions into the crystal lattice will cause an extrinsic absorption in the UV region. 8 In order to circumvent this problem, Mo or Pb ionfree flux systems are desired.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In the process of searching for new borates, cation modulating has been considered to be an effective strategy because the cation modulating can change the cation coordination environment and further influence the overall crystal structure. Al and Ga atoms have similar outer electronic configurations with B atoms and exhibit flexible coordination environment, such as the tetrahedral [AlO 4 ] in K 2 Al 2 B 2 O 7 , pyramidal [AlO 5 ] in NdAl 2.07 (B 4 O 10 )­O 0.6 , and octahedral [GaO 6 ] in BiAlGa 2 (BO 3 ) 4 . Thus, it can be seen that the introduction of Al and Ga atoms can greatly enrich the structural chemistry of borates and further generate useful properties; for example, K 3 Ba 3 Li 2 Al 4 B 6 O 20 F has sufficient SHG response for ultraviolet NLO applications which is composed of infinite [Li 2 Al 4 B 6 O 20 F] double layers.…”
mentioning
confidence: 99%